Elevated high-sensitivity cardiac troponin T serum concentration in subjects with spinal cord injury - Wagner, Björn; Weidner, Norbert; Hug, Andreas (International journal of cardiology, 2023)
Background - The biochemical analysis of high-sensitivity cardiac troponins (hs-cTn) from peripheral blood specimens has been established as biomarker for myocardial injury. Independently of myocardial injury, increased serum hs-cTn concentrations have been described in patients with myopathies. The relevance and frequency of noncardiac hs-cTn elevations in spinal cord injury (SCI) is unknown. Our study aimed to 1) determine the frequency of increased hs-cTn concentrations of supposedly noncardiac origin above the 99th percentile (upper reference limit, URL) in an unselected SCI population and 2) compare the two protagonist analytes cTnT and cTnI with respect to these noncardiac elevations. - Methods - In this monocentric, cross-sectional study, we sampled blood from n = 30 SCI subjects without cardiac symptoms to test for hs-cTnT and hs-cTnI serum concentrations. - Results - 18/30 (60%) of SCI subjects showed increased hs-cTnT concentrations above the URL of 14 ng/l (p < 0.001). In 4 subjects (22.2%) concentrations were >50 ng/l. Moreover, 3 of these four subjects fulfilled the 6-h troponin dynamics criterion for acute myocardial injury in serial hs-cTnT testing. In contrast, no subject demonstrated increased hs-cTnI concentrations according to the URL of 40 ng/l. 6-h troponin dynamics were also unremarkable for hs-cTnI testing. - Conclusions - SCI subjects frequently have increased hs-cTnT concentrations without clinical and hs-cTnI evidence of myocardial injury. Clinicians must be aware of cTnT “skeletal muscle false-positives” in SCI, which applies to elevated baseline cTnT concentrations and troponin dynamics in serial measurements. In case of diagnostic uncertainty, simultaneous analysis of cTnI might be helpful.